HO-1 and CD39: It Takes Two to Protect the Realm - Lee, Ghee Rye; Shaefi, Shahzad; Otterbein, Leo E. (Frontiers in Immunology, 2019)
Cellular protective mechanisms exist that ensure survival and are a fundamental feature of all cells necessary for adaptation to changes in the environment. Indeed, evolution has ensured that the cell is equipped with multiple overlapping families of genes that safeguard against pathogens, injury, stress and dysfunctional metabolic processes. Two of the better-known enzymatic systems, conserved through all species include the heme oxygenases (HO-1/HO-2) and the ectonucleotidases (CD39/73). Each of these systems generates critical bioactive products that regulate the cellular response to a stressor. Absence of these molecules results in the cell being extremely predisposed to collapse and, in most cases, will go on to die. Recent reports have begun to link these two metabolic pathways and what were once exclusively stand-alone are now being found to be intimately interrelated and do so through their innate ability to generate bioactive products including adenosine, carbon monoxide and bilirubin. These simple small molecules elicit profound cellular physiologic responses that impact a number of innate immune responses and participate in the regulation of inflammation and tissue repair. Collectively these enzymes are linked not only the mitochondria as the source of their substrates, but perhaps more importantly, the impact of their products on specific cellular responses. This review will provide a synopsis of the current state of the field regarding how these systems are linked and how they are now being leveraged as therapeutic modalities in the clinic.